PUBLIC PROCUREMENT COMPLIANCE BEHAVIOR AND ITS EFFECT ON QUALITY SERVICE DELIVERY: A CASE STUDY OF THE ELECTRICITY COMPANY OF GHANA (ECG) - Mansaray, Abdul Karim; Lapkoff, Dr. Monica; Little, Anthony (International Journal of Supply Chain Management, 2018)
Purpose: The aim of this study is to examine public procurement compliance behaviour and contrast its effect on quality service delivery. Methodology: The study adopted an explanatory research design in order to achieve the study objectives. The population for this research was made up of the employees of ECG and the customers of ECG, who were systematically sampled. Data was then analyzed through descriptive statistics using the Statistical Package for Social Science. The study employed descriptive statistics, multivariate data analysis as well as regression models Results: Compliance levels were just low in the ranks of ECG; about 15.9%. Non-compliance complements this score by recording an alarming 84.1%. This level of compliance is unacceptable by any standard, no matter how it is justified. A key informant reported that the benefits of non-compliance go to feed the greed of many people in the procurement process. Procurement processes have been owned or possessed by some powerful and influential people who are insulated from the repercussions of poor compliance or, in some cases, non-compliance. Another key informant said "non-compliance has been institutionalized and therefore hard to be isolated and addressed properly". Unique contribution to theory, practice and policy: The study recommends that it would be necessary to strategically work at improving compliance levels through professional procurement training, monitoring of processes for adherence to established policies and standard operating procedures including independent auditing. This process may be slow, drastic and painful; heads may have to roll, reshuffles in leadership and management and forensic audits are needed to prune the past procurement activities that were out of line. To improve service quality, ECG would have to isolate the dimensions that were noted to be weak; being empathy and responsiveness. These may be addressed by professional training and retraining front line personnel and technical rapid response teams to address the concerns of customers with urgency and a human face. Better monitoring and supervision would help to sustain this line of response among ECG stuff.